The anemone, Nematostella vectensis, in Britain: considerations for conservation management - Sheader, M.; Suwailem, A. M.; Rowe, G. A. (Aquatic Conservation: Marine and Freshwater Ecosystems, 1997)
1. The starlet sea anemone, Nematostella vectensis, is a small edwardsiid anemone found in sheltered brackish habitats on the Atlantic and Pacific coasts of North America and on the south and east coasts of England. 2. On eastern Atlantic coasts, this anemone is limited to relatively few sites and has consequently been listed in the IUCN Invertebrate Red Data Book as ‘vulnerable’, receives protection in Britain under The Wildlife and Countryside Act, and is short listed in the UK Biodiversity Action Plan. As detailed information on the ecology of the species is lacking, informed management of existing populations and habitats is difficult. 3. The current distribution in England is outlined, together with a description of habitat characteristics and a list of associated species. 4. The importance of salinity and water flow in determining the occurrence and spatial/temporal patterns of distribution of the species is demonstrated. 5. Population change at three English south coast sites is described and the patterns interpreted in terms of seasonal changes in food availability, salinity and temperature. 6. Although females develop ovaries and are capable of sexual reproduction, males are absent from all south coast populations of N. vectensis and it is concluded that populations at these sites produce all offspring asexually. 7. It is suggested that the species may have been introduced to Europe from North America, though clarification awaits the genetic study of existing populations.